Genotoxicity of multi-walled carbon nanotubes in both in vitro and in vivo assay systems. Issue 4 (June 2013) - Kato, Tatsuya; Totsuka, Yukari; Ishino, Kousuke; Matsumoto, Yoko; Tada, Yukie; Nakae, Dai; Goto, Sumio; Masuda, Shuichi; Ogo, Sayaka; Kawanishi, Masanobu; Yagi, Takashi; Matsuda, Tomonari; et al.
Abstract The genotoxic effects of multi-walled carbon nanotubes (MWCNTs) were examined by using in vitro and in vivo assays. MWCNTs significantly induced micronuclei in A549 cells and enhanced the frequency of sister chromatid exchange (SCE) in CHO AA8 cells. When ICR mice were intratracheally instilled with a single dose (0.05 or 0.2 mg/animal) of MWCNTs, DNA damage of the lungs, analysed by comet assay, increased in a dose-dependent manner. Moreover, DNA oxidative damage, indicated by 8-oxo-7, 8-dihydro-2′-deoxyguanosine and heptanone etheno-deoxyribonucleosides, occurred in the lungs of MWCNT-exposed mice. The gpt mutation frequencies significantly increased in the lungs of MWCNT-treated gpt delta transgenic mice. Transversions were predominant, and G:C to C:G was clearly increased by MWCNTs. Moreover, many regions immunohistochemically stained for inducible NO synthase and nitrotyrosine were observed in the lungs of MWCNT-exposed mice. Overall, MWCNTs were shown to be genotoxic both in in vitro and in vivo tests; the mechanisms probably involve oxidative stress and inflammatory responses.